2018
DOI: 10.1097/md.0000000000011987
|View full text |Cite
|
Sign up to set email alerts
|

Bone quality, and the combination and penetration of cement–bone interface

Abstract: To compare the microstructure, bone quality, and the combination and penetration of cement-bone interface in tissue specimens from patients with osteoarthritis (OA) and rheumatoid arthritis (RA).A total of 80 femoral condyle tissue specimens from 20 OA patients (40 condyles) and 20 RA patients (40 condyles) who underwent total knee arthroplasty at the Department of Orthopaedics in Tengzhou Central People's Hospital were collected between January 2017 and September 2017. According to the random number table met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The main limit of ultrasonography, µ-MRI and PC-CT is an insufficient spatial resolution of these instruments, which is in the order of 10-100 µm/pixel; instead, whilst microCT and SR-CT can reach higher resolutions in the range of 0.35-10 µm/pixel, they mainly work when there is a marked contrast generated by differences in tissue radiopacity. For these reasons, it is not surprising that microCT has been extensively used with hard tissues, such as bones (Mussmann et al, 2017;Song et al, 2018) and teeth (Chałas et al, 2017;Batool et al, 2018;Velozo and Albuquerque, 2019), whose histological composition makes them naturally radiopaque to X-rays. On the other hand, its application on soft tissues is often restricted by the need to employ contrast agents that are largely unspecific with a partial capacity to highlight the presence of different structures within organs (Metscher, 2009;Pauwels et al, 2013;de S e Silva et al, 2015;de Bournonville et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main limit of ultrasonography, µ-MRI and PC-CT is an insufficient spatial resolution of these instruments, which is in the order of 10-100 µm/pixel; instead, whilst microCT and SR-CT can reach higher resolutions in the range of 0.35-10 µm/pixel, they mainly work when there is a marked contrast generated by differences in tissue radiopacity. For these reasons, it is not surprising that microCT has been extensively used with hard tissues, such as bones (Mussmann et al, 2017;Song et al, 2018) and teeth (Chałas et al, 2017;Batool et al, 2018;Velozo and Albuquerque, 2019), whose histological composition makes them naturally radiopaque to X-rays. On the other hand, its application on soft tissues is often restricted by the need to employ contrast agents that are largely unspecific with a partial capacity to highlight the presence of different structures within organs (Metscher, 2009;Pauwels et al, 2013;de S e Silva et al, 2015;de Bournonville et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Again, penetration depth was lower in the periphery, suggesting that applied pressure was stronger centrally than laterally. However, patient-related conditions (e.g., bone density) and differences in the treatment (e.g., pulse lavage, tourniquet, surface drilling, use of laparotomy sponges, and suction) will lead to different penetration depths of the cement in vivo [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-CT analysis of the subchondral bone microstructure is another way to assess the level of detail regarding the pathological changes present in subchondral bone [29]. previously showed that the abnormalities of subchondral bone were present in OA with high bone turnover and subsequent loss of bone mass [8].…”
Section: Discussionmentioning
confidence: 99%